A novel formulation technology for baculoviruses protects biopesticide from degradation by ultraviolet radiation - Kenneth Wilson (Nature Portfolio, 2020)
Abstract Biopesticides are biological pest control agents that are viewed as safer alternatives to the synthetic chemicals that dominate the global insecticide market. A major constraint on the wider adoption of biopesticides is their susceptibility to the ultraviolet (UV: 290–400 nm) radiation in sunlight, which limits their persistence and efficacy. Here, we describe a novel formulation technology for biopesticides in which the active ingredient (baculovirus) is micro-encapsulated in an ENTOSTAT wax combined with a UV absorbant (titanium dioxide, TiO2). Importantly, this capsule protects the sensitive viral DNA from degrading in sunlight, but dissolves in the alkaline insect gut to release the virus, which then infects and kills the pest. We show, using simulated sunlight, in both laboratory bioassays and trials on cabbage and tomato plants, that this can extend the efficacy of the biopesticide well beyond the few hours of existing virus formulations, potentially increasing the spray interval and/or reducing the need for high application rates. The new formulation has a shelf-life at 30 °C of at least 6 months, which is comparable to standard commercial biopesticides and has no phytotoxic effect on the host plants. Taken together, these findings suggest that the new formulation technology could reduce the costs and increase the efficacy of baculovirus biopesticides, with the potential to make them commercially competitive alternatives to synthetic chemicals.